Esculetin as a Bifunctional Antioxidant Prevents and Counteracts the Oxidative Stress and Neuronal Death Induced by Amyloid Protein in SH-SY5Y Cells - Letizia Pruccoli; Fabiana Morroni; Giulia Sita; Patrizia Hrelia; Andrea Tarozzi (Antioxidants, 2020)
Oxidative stress (OS) appears to be an important determinant during the different stages of progression of Alzheimer’s Disease (AD). In particular, impaired antioxidant defense mechanisms, such as the decrease of glutathione (GSH) and nuclear factor erythroid 2 (NF-E2)-related factor 2 (Nrf2), a master regulator of antioxidant genes, including those for GSH, are associated with OS in the human AD brain. Among the neuropathological hallmarks of AD, the soluble oligomers of amyloid beta (A) peptides seem to promote neuronal death through mitochondrial dysfunction and OS. In this regard, bifunctional antioxidants can exert a dual neuroprotective role by scavenging reactive oxygen species (ROS) directly and concomitant induction of antioxidant genes. In this study, among natural coumarins (esculetin, scopoletin, fraxetin and daphnetin), we demonstrated the ability of esculetin (ESC) to prevent and counteract ROS formation in neuronal SH-SY5Y cells, suggesting its profile as a bifunctional antioxidant. In particular, ESC increased the resistance of the SH-SY5Y cells against OS through the activation of Nrf2 and increase of GSH. In similar experimental conditions, ESC could also protect the SH-SY5Y cells from the OS and neuronal death evoked by oligomers of A1–42 peptides. Further, the use of the inhibitors PD98059 and LY294002 also showed that Erk1/2 and Akt signaling pathways were involved in the neuroprotection mediated by ESC. These results encourage further research in AD models to explore the efficacy and safety profile of ESC as a novel neuroprotective agent.